Choline chloride/urea as a green and efficient deep eutectic solvent in three-component and four-component synthesis of novel pyrazole and pyrano[2,3-c] pyrazole derivatives with antibacterial and antifungal activity - Habeeb Naser, Israa; Thoulfikar A. Alamir, Hassan; Al-Shukarji, Ali Hisham; Ahmed, Batool Ali; Qassem, Talal Aziz; Kamal, Maher; Almeleebia, Tahani M.; Alwaily, Enas R.; Hasan Kadhum, Eftikhaar; Alawadi, Ahmed; Alsalamy, Ali (Frontiers in Chemistry, 2024)
Choline chloride/urea was used as a green deep eutectic solvent in three-component reaction of hydrazine/phenylhydrazine, malononitrile and aromatic aldehydes for synthesizing pyrazole derivatives and in the four-component reaction of methyl/ethyl acetoacetate, hydrazine/phenylhydrazine, malononitrile and aromatic aldehydes for synthesizing pyrano[2,3-c]pyrazole derivatives. Elemental analysis, 1 H, and 13 C NMR spectroscopy were used to confirm the structure of the synthesized pyrazole and pyrano[2,3-c] pyrazole derivatives. The antimicrobial effects of the synthesized pyrazole and pyrano[2,3-c] pyrazole derivatives were investigated. In antimicrobial tests, instructions of clinical and laboratory standards institute were used.Antimicrobial study was done on pathogenic gram-positive and gram-negative species, specialized aquatic strains, and fungal species. Using choline chloride/urea, novel pyrazole derivatives and pyrano[2,3-c]pyrazole derivatives were synthesized, and other derivatives were synthesized with higher efficiency in less time than some previously reported methods. MIC (minimum inhibitory concentration) and MBC (minimum bactericidal concentration) obtained for derivatives were higher than some antibiotic drugs. Synthesis and report of new derivatives of pyrazole and pyrano[2,3-c]pyrazole, investigation and report of their antimicrobial properties on gram-positive, gram-negative, specialized aquatic and fungal species are among the novelties and importance of this study.